The Limit of Downsizing Dielectric-Filled Slotted Waveguide Antennas - Bachbauer, Felix; Lomakin, Konstantin; Sippel, Mark; Gold, Gerald (2024 IEEE Wireless and Microwave Technology Conference, WAMICON 2024, 2024)
Miniaturization of a slotted waveguide antenna has its limits. Therefore, this paper examines the extent to which simple resonant waveguide slot antennas can be miniaturized using a dielectric filling and when the minimum size of the antenna is reached. To this end, the shrinking of the wavelength change due to the filling is initially considered. Afterwards, it is analytically shown, how this affects the function of the waveguide antenna. Then, suitable relative permittivity values for various applications are determined on the basis of given design values. Finally, an antenna is designed according to the previous considerations and then both manufactured and characterized.
CRIS-Team Scopus Importer:2024-05-31
Keywords: Additive manufacturing; dielectric filled waveguide; slot antenna; waveguide antennas